Evaluation of Mesenchymal Stem Cell Therapy for Sepsis: A Randomized Controlled Porcine Study - Horak, Jan; Nalos, Lukas; Martinkova, Vendula; Tegl, Vaclav; Vistejnova, Lucie; Kuncova, Jitka; Kohoutova, Michaela; Jarkovska, Dagmar; Dolejsova, Martina; Benes, Jan; Stengl, Milan; Matejovic, Martin (Frontiers in Immunology, 2020)
Background and objectives: Treatment with mesenchymal stem cells (MSCs) has elicited considerable interest as an adjunctive therapy in sepsis. However, the encouraging effects of experiments with MSC in rodents have not been adequately studied in large-animal models with better relevance to human sepsis. Here, we aimed to assess safety and efficacy of bone marrow-derived MSCs in a clinically relevant porcine model of progressive peritonitis-induced sepsis. Methods: Thirty-two anesthetized, mechanically ventilated, and instrumented pigs were randomly assigned into four groups (n = 8 per group): 1) sham-operated group (CONTROL); 2) sham-operated group treated with MSCs (MSC-CONTROL); 3) sepsis group with standard supportive care (SEPSIS,); and 4) sepsis group treated with MSCs (MSC-SEPSIS). Peritoneal sepsis was induced by inoculating cultivated autologous feces. MSCs (1×106/kg) were administered intravenously at 6 h after sepsis induction. Measurements and main results: Before, 12, 18, and 24 h after the induction of peritonitis, we measured systemic, regional, and microvascular hemodynamics, multiple-organ functions, mitochondrial energy metabolism, systemic immune-inflammatory response, and oxidative stress. Administration of MSCs in the MSC-CONTROL group did not elicit any measurable acute effects. Treatment of septic animals with MSCs failed to mitigate sepsis-induced hemodynamic alterations or the gradual rise in Sepsis-related organ failure assessment scores. MSCs did not confer any protection against sepsis-mediated cellular myocardial depression and mitochondrial dysfunction. MSCs also failed to modulate the deregulated immune-inflammatory response. Conclusions: Intravenous administration of bone marrow-derived MSCs to healthy animals was well tolerated. However, in this large-animal, peritonitis-induced sepsis model, MSCs were not capable of reversing any of the sepsis-induced disturbances in multiple biological, organ, and cellular systems.